From Louisville to Liddell: Schools, Rhetorical Neutrality, and the Post-Racial Equal Protection Clause - Cedric Merlin Powell (Washington University Journal of Law & Policy, 2012)
As we commemorate the inspiring legacy of Minnie Liddell and countless liberation activists who struggled for substantive equality in education for generations, it is appropriate to reflect on the current state and future of urban education. The school desegregation (integration) movements in Louisville, Kentucky and St. Louis, Missouri can best be understood as two distinct permutations of the Process Theory. In Louisville, the process-orientation tilts toward individual choice—neighborhood schools are at the core of all of the discussions about student assignment plans. Conversely, in St. Louis, the seminal process initiative is charter schools. Neither processual outcome addresses the present day effects of past discrimination, so there remain substantial systemic inequalities that have not been addressed. This is the quintessential problem with neutrality—it preserves the status quo. It is interesting to note that whether desegregation is achieved through political compromise and collaboration, as in St. Louis, or by court order, as in Louisville, the outcomes focus on process-based values like access (or choice), not substantive equality. On some level, the power of "choice" is overvalued. So, while there is "access," this means something dramatically different when city and suburban schools are compared. This is the classically neutral rationale of access, which is at the heart of the Process Theory. Part I of this Essay posits the concept of Rhetorical Neutrality and sets the context for the Court‘s race jurisprudence in Brown and its progeny. Building upon this critique of neutrality, Part II references the Process Theory and unpacks it to critique the process-based outcomes in Louisville and St. Louis. Part III concludes with a critique of a Kentucky statute that preserves the "right" to attend neighborhood schools and the limited success of the St. Louis voluntary school assignment plan. Louisville and St. Louis represent the current state of urban education in America.
Keywords: Liddell; Minnie Liddell; school desegregation; Louisville school; desegregation; Process Theory; charter schools; Brown v. Board of Education